Role of Collectors and Depressants in Mineral Flotation: A Theoretical Analysis Based on Extended DLVO Theory - Xing, Y.; Gui, X.; Karakas, F.; Cao, Y. (MDPI AG, 2017)
A theoretical analysis was conducted to study the role of collectors and depressants in flotation, based on the extended Derjaguin–Landau–Verwey–Overbeek (DLVO) theory, where the hydrophobic force is considered. The collector-coated hydrophilic particle and the depressant-coated hydrophobic particle are simplified to a sphere uniformly covered with respectively hydrophobic and hydrophilic nanometer-sized hemispherical asperities of identical radius. Results show that the role of a collector in bubble–particle attachment is to create an attractive hydrophobic force and thus overcome the repulsive van der Waals and electrostatic forces. Moreover, increasing the length of the hydrophobic part of the collector molecule is a more effective way to enhance flotation recovery, compared to increasing the collector concentration. For a depressant, however, its function mechanism is to create a strong electrostatic double-layer force, while the suppression of the hydrophobic force plays a secondary role in decreasing the bubble–particle attachment barrier. The depressant molecule length is also a dominant parameter in designing a powerful depressant.
Keywords: flotation; collector; depressant; surface roughness; extended DLVO theory